Economics of natural resources and the environment - Pearce, David W., ....-; Turner, Kerry R., ....- (Baltimore : The Johns Hopkins University Press, 1990)
Economics of Natural Resources and the Environment brings together the approaches of natural resource economics and environmental economics to provide a comprehensive overview of the economics of national, international, and global environmental problems. A unifying theme throughout the book is the concept of "sustainable development", defined as "maximizing the net benefits of economic development while maintaining the services and quality of natural resources over time."
Keywords: Environmental economics; Natural resources Management; Social Sciences and Humanities. Economics Environmental Economics; Sustainable development